Menjaga Keseimbangan Emosi Mahasiswa Muslim: Analisis Regulasi Emosi melalui Praktik Keagamaan - Udizca Nurvithasary; Elia Firda Mufidah; Andini Poncogati; Livia Zahrotun Nafisah; Nandhita Putri Rahmahwati (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
This study aims to assess the level of emotional regulation among Muslim university students, analyze the impact of religious practices such as reciting the Qur'an and engaging in dhikr on emotional regulation, and identify the relationship between emotional regulation, psychological well-being, and social maturity. A quantitative approach with a descriptive design was employed. The sample consisted of 103 active Muslim students from various universities in Indonesia, selected through purposive sampling and assessed using an emotional regulation instrument. The data were analyzed using descriptive statistics. The findings revealed that most students demonstrated a good level of emotional regulation, with female students tending to have better emotional regulation than their male counterparts. Furthermore, religious practices such as Qur'anic recitation and dhikr were found to have a positive impact on emotional regulation, contributing to enhanced psychological well-being and social maturity. This study provides significant insights into the relationship between religious practices and emotional regulation, and offers recommendations for the development of psychological support programs grounded in Islamic values to improve students’ well-being and adaptive capacities in facing academic and social challenges.